Senescent Tissue-Resident Mesenchymal Stromal Cells Are an Internal Source of Inflammation in Human Osteoarthritic Cartilage - Liu, Wenguang; Brodsky, Alexander S.; Feng, Meng; Liu, Yajun; Ding, Jing; Jayasuriya, Chathuraka T.; Chen, Qian (Frontiers in Cell and Developmental Biology, 2021)
Human osteoarthritic cartilage contains not only chondrocytes (OAC), but also mesenchymal stromal cells (OA-MSC), whose abundance increases during OA. However, it is not clear how OA-MSC contributes to OA pathogenesis. Here, we show that aging OA-MSC plays an important role in cell senescence, fibrosis, and inflammation in cartilage. Protein array analysis indicates that OA-MSC expresses pro-inflammatory senescence associated secretory phenotype (SASP) including IL-1, IL-6, IL-8, and CXCL1, 5, and 6, which play key roles in OA pathogenesis. OAC is a main recipient of the inflammatory signals by expressing receptors of cytokines. RNAseq analysis indicates that the transition from normal cartilage stromal cells (NCSC) to OA-MSC during aging results in activation of SASP gene expression. This cell transition process can be recapitulated by a serial passage of primary OAC in cell culture comprising 1) OAC dedifferentiation into NCSC-like cells, and 2) its subsequent senescence into pro-inflammatory OA-MSC. While OAC dedifferentiation is mediated by transcriptional repression of chondrogenic gene expression, OA-MSC senescence is mediated by transcriptional activation of SASP gene expression. We postulate that, through replication-driven OAC dedifferentiation and MSC senescence, OA-MSC becomes an internal source of sterile inflammation in human cartilage joint.